Low-cost sensors for fine particulate matter (PM2.5) characterization in a high Andean city - Ulloa Ninahuamán, Jesús (2022)
Huancayo is a city located at Peruvian Central Andes and presents air pollution problems related to particulate matter (PM), especially fine fraction (PM2.5). Given the high costs of air quality monitoring network infrastructure and the need for more detailed information, the objective of the study is to evaluate the temporal variation and source zones of PM2.5 through the use of low-cost sensors installed at three sites in the city of Huancayo. PurpleAir PA-II model PMS5003 sensors were employed from August 2018 to June 2019. The dataset was subjected to statistical tests to evaluate temporal changes. Backtrajectories were calculated through the HYSPLIT model for source zone identification. The results show reasonable agreement with other reference monitoring. The importance of the use of low-cost sensors in the establishment of an air quality monitoring network in high Andean areas is highlighted and the determination of emission sources.